Studies on Lanthanide (III) Complexes with N-Substituted Thioureas - Kalyani, S.A.; Murty, A.S.R. (Asian Journal of Chemistry, 2010)
Lanthanide (III) complexes of N-thioureas of the type [MX3–mnL] Xm2H2O [M = Sm(III), Eu(III), Dy(III) and Y(III); X = NO–3, Cl–; L=m-chlorophenyl thiourea (m-Clptu), p-chlorophenyl thiourea (p-Clptu), m-hydroxy phenyl thiourea (m-OHptu); m = 0, 1 and n = 3, 4] have been synthesized and characterized by elemental analysis, conductivity, magnetic moment, IR and visible spectra and thermal studies. All complexes are nonelectrolytes except [Sm(NO3)2(m-OHptu)4] NO3·2H2O which is 1 : 1 electrolyte. Barring Y(III) complexes, all others exhibit paramagnetism. While IR spectral data unequivocally suggest S bonding of ligands, results from visible spectra evaluate the extent of covalency.